Finite element modelling of interface shear strength at concrete-to-concrete bond - Mohamad, Mazizah Ezdiani (2015)
Interface shear strength between concrete layers cast at different times plays an important role to provide monolithic behavior of composite concrete. In this paper, a computational modeling approach is used to study the concrete-to-concrete bond behavior between two concrete layers cast at different times; concrete base and concrete topping. The compressive strength of the concrete base is 40 N/mm2, while the concrete topping is 25 N/mm2. Finite Element Analysis (FEA) package ABAQUS 6.12 is used to model the bond interaction of concrete-to-concrete layers, which is then verified with the experimental test. Four specimens with different types of surface textures are - -brushing in transverse direction and projecting steel reinforcement crossing the interface. Failure of the bonded interfaces is modeled with cohesive zone model (CZM) approach with zero thickness interface element where the governing parameters are - meanwhile, the projecting steel surface is modeled with Modified Drucker-Prager/Cap-Plasticity Model (CPM) approach with 1 mm thickness of interface element. The parameters used in the analysis include interface shear strength, fracture energy and elastic shear stiffness for CZM approach. The CPM parameters for modeling projecting steel surface are cohesion, interface friction angle, cap eccentricity parameter, initial cap yield surface position, flow stress ratio, yield stress at interface. The study shows that the difference between the modeled and experimental results is relatively small and therefore shows the capability of the finite element analysis to carry out interface analysis.